A Case with Severe Endometriosis, Ovarian Hyperstimulation Syndrome, and Isolated Unilateral Pleural Effusion after IVF - Negjyp Sopa; Elisabeth Clare Larsen; Anders Nyboe Andersen (Case Reports in Obstetrics and Gynecology)
We present a very rare case of right-sided isolated pleural effusion in a patient with severe endometriosis who, in relation to in vitro fertilization (IVF), developed ovarian hyperstimulation syndrome (OHSS). Earlier laparotomy showed grade IV endometriosis including endometriotic implants of the diaphragm. The patient had no known risk factors for OHSS and only a moderate number of oocytes aspirated. She received, however, repeated hCG injections for luteal support. The patient did not achieve pregnancy but was hospitalized due to pain in the right side of the chest and dyspnoea. A chest computed tomography (CT) showed a pleural effusion on the right side. Total of 1000 ml of pleural fluid was drained after a single thoracentesis. After three days, the symptoms and fluid production ceased. Ascites is a common finding in OHSS, but pleural effusions are rare. Further, isolated pleural effusions have not previously been described in a patient with endometriosis. We suggest that the repeated hCG injections induced effusions from the endometriotic lesions at the diaphragm and as a consequence this patient developed isolated hydrothorax.